2006
DOI: 10.1111/j.1471-4159.2006.04151.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural compound n‐butylidenephthalide derived from Angelica sinensis inhibits malignant brain tumor growth in vitro and in vivo3

Abstract: The naturally-occurring compound, n-butylidenephthalide (BP), which is isolated from the chloroform extract of Angelica sinensis (AS-C), has been investigated with respect to the treatment of angina. In this study, we have examined the antitumor effects of n-butylidenephthalide on glioblastoma multiforme (GBM) brain tumors both in vitro and in vivo. In vitro, GBM cells were treated with BP, and the effects of proliferation, cell cycle and apoptosis were determined. In vivo, DBTRG-05MG, the human GBM tumor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 24 publications
2
107
0
Order By: Relevance
“…Release of active E2F triggers the activation of a number of genes that are required for the G 0 /G 1 -S phase transition. In previous studies, regulation of p21 expression and Rb phosphorylation were shown to be responsible for cell cycle arrest in the G 0 /G 1 phase in glioma cells (Choi et al, 2008;Tsai et al, 2006). GSK3 is a multifunctional serine/threonine kinase that reg β ulates various cellular pathways involved in the cell cycle, proliferation, differentiation, and apoptosis (Blomgren et al, 2007;He et al, 2003;Miyashita et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Release of active E2F triggers the activation of a number of genes that are required for the G 0 /G 1 -S phase transition. In previous studies, regulation of p21 expression and Rb phosphorylation were shown to be responsible for cell cycle arrest in the G 0 /G 1 phase in glioma cells (Choi et al, 2008;Tsai et al, 2006). GSK3 is a multifunctional serine/threonine kinase that reg β ulates various cellular pathways involved in the cell cycle, proliferation, differentiation, and apoptosis (Blomgren et al, 2007;He et al, 2003;Miyashita et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies (Tsai et al, 2005(Tsai et al, , 2006, we demonstrated the antitumoral effects of BP on glioblastoma multiforme (GBM) brain tumors both in vitro and in vivo. In this study, we selected HepG2 and J5 HCC for further investigations because of its poor prognosis and because it requires a new strategy in clinical practice.…”
Section: Bp-related Growth Inhibition and Apoptosis Of Hcc Cells In Vmentioning
confidence: 99%
“…Diels (AS), also referred to as dong quai or danggui, a traditional Chinese medicine for menopausal symptoms (Yim et al, 2000;Ye et al, 2001a,b), has been clinically administrated for several gynecological symptoms in the United States (Abebe, 2002). In our previous study, the chloroform extract of AS and N-butylidenephthalide (BP), derived from the chloroform extract of AS, both revealed dramatic antitumor effects, causing growth arrest and apoptosis of malignant brain tumors in vitro and in vivo (Tsai et al, 2005(Tsai et al, , 2006. To date, little is known about its antitumor effects on HCC cells.…”
mentioning
confidence: 98%
“…The natural compound n-butylidenephthalide (BP), isolated from the chloroform extract of Angelica sinensis, has been reported to have antitumor activity in glioblastoma multiforme (GBM), [1][2][3][4] prostate cancer, 5,6 oral squamous cell carcinoma, 7 lung cancer, 8 and hepatoma. 9 In particular, BP has been developed to treat brain tumors due to its ability to permeate through the blood-brain barrier and enter into the brain.…”
Section: Introductionmentioning
confidence: 99%
“…9 In particular, BP has been developed to treat brain tumors due to its ability to permeate through the blood-brain barrier and enter into the brain. 1 BP induces Nur77-mediated apoptosis via the protein kinase C/JNK pathway. 4,7,9,10 BP downregulates the expression of S-phase kinase-associated protein (Skp2), which leads to an increase in p16 and p21 expression, causing G 0 /G 1 arrest.…”
Section: Introductionmentioning
confidence: 99%